2016
DOI: 10.1016/j.seps.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Does class matter more than school? Evidence from a multilevel statistical analysis on Italian junior secondary school students

Abstract: This paper assesses the differences in educational attainments between students across classes and schools they are grouped by, in the context of Italian educational system. The purpose is to identify a relationship between pupils' reading test scores and students' characteristics, stratifying for classes, schools and geographical areas. The dataset contains detailed information about more than 500,000 students at the first year of junior secondary school in the year 2012/2013. By means of multilevel linear mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…Therefore, INVALSI own statistical analyses reveal that there are not striking differences in the results that can be obtained when considering alternatively these two subjects. Applications of similar models to the set of reading scores instead of mathematics seem to confirm the main phenomena that are described in the present research (see preliminary results in Masci et al 2016).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, INVALSI own statistical analyses reveal that there are not striking differences in the results that can be obtained when considering alternatively these two subjects. Applications of similar models to the set of reading scores instead of mathematics seem to confirm the main phenomena that are described in the present research (see preliminary results in Masci et al 2016).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 87%
“…, J (R) ). While in theory adding class-level variables can be interesting to understand the key determinants of students achievement at that level of analysis, this is not the primary scope of the paper (the interested reader can look at Masci et al 2016, where we focus on this topic). The estimation of class effects, in the present work, should be interpreted as a byproduct of the main analysis, with the sole interest on showing the relative weight of variance at student, class and school levels.…”
Section: Boxplot Of School Random Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we present the semiparametric mixed effects model (Section 2.1), the EM algorithm for the estimation of its parameters (Section 2.2) and a simulation study (Section 2.3). Since we know from previous research on Italian data that there are patterns of student achievements across different Italian schools (Agasisti et al ., ; Masci et al ., , ), we are interested in evaluating how the association between previous and current student test scores changes across different Italian schools and, in particular, in identifying subpopulations of schools within which this association is identical. Therefore, the model that we develop is a two‐level linear model (in the application, students represent level 1 and schools represent level 2) with a discrete distribution with a finite number of support points on the random effects.…”
Section: Model Methods and Simulation Studymentioning
confidence: 99%
“…() and Masci et al . (, ) observed that the percentage of variability in student attainments in INVALSI tests explained by the random effect depends on the geographical macroarea and differs between mathematics and reading performances. In particular, this percentage is higher in mathematics and especially in southern Italy, reaching peaks of 20%.…”
Section: Introductionmentioning
confidence: 99%